Diagnostics of introduction value of herbs of natural flora in the conditions of Mangystau - Imanbayeva, А.А.; Belozerov, I.F.; Ishmuratova, М.Yu. (KSU publ., 2018)
At the article the results of assessment of introductive value of herbs of natural flora of Mangyshlak for planting in the Mangyshlak experimental botanical garden are presented. Valued scale included 24 diagnostic signs separated into 4 groups: biological stability (hot-, dry-, winter-stability, resistant to disease and pest, substrate requirement), decorative properties and habitus (general decorative properties, length and esthetic properties of flowering and fructification), reproductive ability (seed or vegetative reproduction), practicalbiological and scientific meaning (using as decorative, phytomeliorative, food, medical or technical plant). Indexes of value of herbs varied from «reduced» (V class, 45 balls) till «very high» (IX class, 83 balls). The maximum ball belongs to Tamarix ramisissimum, the minimum — Solanum persicum. The assessment of introduction value of 127 species of herbs of natural flora of Mangystau region is developed. The results are shown that «extremely low» introduction value was diagnosed 1.6 % studied species; «very low» — 3.9 %; «low» — 8.7 %; «reduced» — 15.7 %; «higher» — 22.8 %; «high» — 13.4 % и «very high» — 7.1 %. On the base of diagnostic of introduction value of herbs of natural flora is producing the collection of herbs.
Маңғышлақ табиғи флора жағдайындағы дəрілік өсімдіктердің интродукциялық құндылықтарының диагностикасы
Диагностика интродукционной ценности лекарственных растений природной флоры в условиях Мангышлака
Keywords: introduction; herb; natural flora; Mangyshlak experimental botanical garden; value; diagnostics